2006
DOI: 10.1111/j.1399-5448.2006.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Does lean rather than fat mass provide the link between birth weight, BMI, and metabolic risk? EarlyBird 23

Abstract: In boys, the relationships between birth weight, triglycerides, and lean mass are consistent with the hypothesis. Overall, our findings provide limited evidence in support of the argument that higher birth weight predicts lower metabolic risk because it marks programming of more lean mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 9 publications
1
24
0
1
Order By: Relevance
“…As reported in previously published articles, the programming of less lean mass by suboptimal fetal growth has been observed in which body composition measurements were obtained by dual energy x-ray absorptiometry (DXA) (32,35), by anthropometric methods (36), or by bioelectrical impedance (33). Conversely, the results showed that there were no PPAR␥-2 gene polymorphism-related differences in the relationship between Z score birth weight and later body fat distribution.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…As reported in previously published articles, the programming of less lean mass by suboptimal fetal growth has been observed in which body composition measurements were obtained by dual energy x-ray absorptiometry (DXA) (32,35), by anthropometric methods (36), or by bioelectrical impedance (33). Conversely, the results showed that there were no PPAR␥-2 gene polymorphism-related differences in the relationship between Z score birth weight and later body fat distribution.…”
Section: Discussionmentioning
confidence: 42%
“…Several recent studies found associations between low birth weight and increased metabolic risk of cardiovascular disease by programming small proportion of lean mass later in life (33,34). As reported in previously published articles, the programming of less lean mass by suboptimal fetal growth has been observed in which body composition measurements were obtained by dual energy x-ray absorptiometry (DXA) (32,35), by anthropometric methods (36), or by bioelectrical impedance (33).…”
Section: Discussionmentioning
confidence: 65%
“…Extrapolating, excessive GWG might increase the risk of offspring obesity. However, associations between birthweight and childhood or adulthood BMI do not necessarily imply increased risk of offspring obesity; indeed, some authors have shown that higher birthweight may be linked to a greater lean mass in later life, rather than fat mass [11]. Accurate determination of body fat mass in infant and child provides a more apposite measure, and studies from the UK ALPSAC cohort and the Southampton Women's Survey, amongst others, have suggested that it is the fatter, not necessarily the heavier infant, who is at risk of becoming the fatter child [12 && ,13].…”
Section: Gestational Weight Gain and Childhood Obesitymentioning
confidence: 95%
“…A caveat is that, while large infant birth weight for gestational age is generally an indicator of excess fat mass, it may also reflect other growth parameters such that a subset of large infant birth weight for gestational age infants may have increased lean mass (62,63). Risk factors for large infant birth weight for gestational age include maternal obesity and maternal gestational diabetes (64,65) with African-American women exhibiting risk at lower maternal BMI thresholds (66).…”
Section: Prenatal and Postnatal Influencesmentioning
confidence: 99%